IMPLICATION OF GENE ACTION AND HERITABILITY UNDER STRESS AND CONTROL CONDITIONS FOR SELECTION IRON TOXICITY TOLERANT IN RICE - Yudhistira Nugraha; Sintho Wahyuning Ardie; Munif Ghulamahdi; Suwarno Suwarno; Hajrial Aswidinnoor (AGRIVITA, Journal of Agricultural Science, 2016)
Iron toxicity is major constraint of rice production in irrigated-lowland of tropical regions. Improvement the tolerance of the rice cultivar to iron toxicity needs the information some genetics parameters of the selected characters. Here we study the estimation of gene action and heritability of the grain yield and its component under iron-toxic stress and control field conditions in rice. The iron-toxic tolerant rice cultivars, Pokkali and Mahsuri were crossed with the sensitive cultivar, Inpara5 to develop six generation populations. The breeding materials were grown in the iron toxicity site and control in Taman Bogo, Lampung Indonesia. The sensitive parent and BC1P1 had lower stress tolerance index (STI) compared to the tolerant parent F1, F2 and BC1P2.  Most of the characters including the grain yield were fitted the best model in five parameters which were more prominent with interactive epistasis of duplicate and complementary gene action.  The heritability’s under control were more higher compared to iron toxicity stress condition. Delaying selection to later generations and combining with the shuttle breeding between stressed and controlled environments were the best strategy for improving the grain yield and tolerance to iron toxicity in rice.